Allogeneic transplantation using CD34+ selected peripheral blood progenitor cells combined with non‐mobilized donor T cells for refractory severe aplastic anaemia. (7th February 2017) - Purev, Enkhtsetseg; Tian, Xin; Aue, Georg; Pantin, Jeremy; Vo, Phuong; Shalabi, Reem; Reger, Robert N.; Cook, Lisa; Ramos, Catalina; Cho, Elena; Worthy, Tat'yana; Khuu, Hanh; et al.
Summary: Allogeneic haematopoietic stem cell transplantation is curative for severe aplastic anaemia (SAA) unresponsive to immunosuppressive therapy. To reduce chronic graft‐ versus ‐host disease (GVHD), which occurs more frequently after peripheral blood stem cell (PBSC) transplantation compared to bone‐marrow transplantation (BMT), and to prevent graft rejection, we developed a novel partial T‐cell depleted transplant that infuses high numbers of granulocyte colony‐stimulating factor‐mobilized CD34 + selected PBSCs combined with a BMT‐equivalent dose of non‐mobilized donor T‐cells. Fifteen patients with refractory SAA received cyclophosphamide, anti‐thymocyte globulin and fludarabine conditioning, and were transplanted with a median 8 × 10 6 CD34 + cells/kg and 2 × 10 7 non‐mobilized CD3 + T‐cells/kg from human leucocyte antigen‐matched sibling donors. All achieved sustained engraftment with only two developing acute and two developing chronic GVHD. With a 3·5‐year median follow‐up, 86% of patients survived and were transfusion‐independent. When compared to a retrospective cohort of 56 bone‐marrow failure patients that received the identical transplant preparative regimen and GVHD prophylaxis with the exception that the allograft contained unmanipulated PBSCs, partial T‐cell depleted transplant recipients had delayed donor T‐cell chimerism and relative reduction of 75% in the incidence of acute grade II‐IV GVHD (13% vs. 52%; P = 0·010) and of 82% in chronic GVHD (13% vs. 72%; P = 0·0004). In multivariate analysis, partial T‐cell depleted transplants remained significantly associated with a reduced risk of GVHD. In conclusion, for patients with refractory SAA, this novel transplant strategy achieves excellent engraftment and survival when compared to unmanipulated PBSC transplants and dramatically reduces the incidence of both acute and chronic GVHD.